STUDENTS' CREATIVE THINKING ANALYSIS OF SPLTV MATERIALS THROUGH VIRTUAL LEARNING REVIEWED FROM BEGINNING MATHEMATICS ABILITY - Muhammad Najib Siraj; Ishaq Nuriadin (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Mathematical creative thinking ability is certainly different for each student based on their initial mathematical abilities. Virtual learning has become the main learning process during a pandemic. The purpose of this study was to analyze how students' creative thinking skills on SPLTV material through virtual learning were based on students' initial mathematical abilities. The subjects in this study were students of class X SMA Malahayati Islamic School totaling 149 students, which were then taken 3 students based on their initial mathematical abilities. This study used the descriptive qualitative method. Data analysis in this study is to describe the results of student interviews and answers. Checking the validity of the data using data triangulation techniques. The results showed that students with high and moderate initial abilities had mathematical creative thinking skills from the ground up and needed to be honed again. Meanwhile, students with low initial ability cannot think creatively at all. Learning in virtual classes greatly affects the learning process, especially student learning outcomes. So that mathematical creative thinking skills are strongly influenced by students' initial mathematical abilities and student learning processes.